Planning For Terminal Service Integration and Parking Facility Improvement at Muara Angke Port, North Jakarta - Michiels, Alfian; Sihombing, Sarinah; Indrawan, Rully; Gunawan, Aang; Setiawan, Edhie Budi (Dinasti Review, 2025)
This study aims to analyze the influence of parking inventory and parking utilization on terminal services and facility improvements at Muara Angke Port, North Jakarta. The background of this research is based on the current condition where the terminal is not yet located within the port area, requiring users to walk more than one kilometer and/or use other modes of transportation to reach the terminal. This research adopts a quantitative approach using survey methods through the distribution of questionnaires to respondents consisting of three main groups: regulators (port authorities), operators (terminal and parking managers), and consumers (passengers). The study involved a sample of 240 respondents, in accordance with the recommended number of indicators in statistical analysis as proposed by Hair et al. (2014). Primary data were collected through questionnaires, while secondary data were obtained from literature, scientific journals, and relevant regulations. Data analysis was conducted using Structural Equation Modeling (SEM) with the assistance of Smart PLS software. The model employed includes the outer model to test validity and reliability, and the inner model to test causal relationships among variables. The findings indicate that both parking inventory and parking utilization have a positive and significant influence on terminal services and facility improvements. These findings suggest that optimizing the parking function can serve as a basis for planning the integration of the terminal into the port area to enhance user comfort and service efficiency.